Influence of Problem-Based Learning Models Improving Students’ Problem-Solving Skills - Dakabesi, Daud (Jurnal Beta Kimia, 2025)
One cognitive skill needed to meet the demands of the complex and dynamic development of the twenty-first century is problem-solving. Therefore, this research aimed to investigate how well 126 students understood chemical difficulties about reaction rate material both individually and collaboratively. Only a posttest is applied in this study's quasi-experimental research design. Sixty-two learners in the experimental class received treatment using a Problem-Based Learning (PBL) model, while sixty-four learners in the learning control group received treatment using traditional methods. According to the findings, pupils in the experimental class were more adept at solving problems than those in the control group. The study's findings also show how collaborative problem-solving significantly aids students' attempts to solve chemical challenges.